Socio-Scientific Controversial Issues in 1st Cycle of Basic Education - Fábio Ribeiro; Celina Tenreiro Vieira (Universidade Estadual Paulista Júlio de Mesquita Filho, 2014)
Assuming the importance of science education, from early years, aiming to educate citizens capable of thinking critically and act in scientific and technological contexts, a study was carried out in order to develop learning situations focused on controversial socio-scientific issues to promote students' argumentation skills and scientific knowledge building / mobilization. The study was based on a qualitative methodology, following an action research plan. It was conducted with a class of 3th grade, having been addressed controversial socio-scientific issues, framed in science curriculum topics, using strategies of debate, role-play and argumentative essays. Data was collected using an analyzing instrument of student´s oral and written productions. In data analysis the privileged technique was content analysis. The results suggest that students mobilized requested scientific knowledge, showing improvement in the effective use of argumentation skills required. This allows us to conclude that the approach of controversial socio-scientific issues contributes to the promotion students´ argumentation skills as well as for scientific knowledge construction / mobilization.